2013
DOI: 10.1371/journal.pone.0055679
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Modernization among Bolivian Amerindians

Abstract: BackgroundPhysical inactivity is a growing public health problem, and the fourth leading risk factor for global mortality. Conversely, indigenous populations living traditional lifestyles reportedly engage in vigorous daily activity that is protective against non-communicable diseases. Here we analyze physical activity patterns among the Tsimane, forager-horticulturalists of Amazonian Bolivia with minimal heart disease and diabetes. We assess age patterns of adult activity among men and women, test whether mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 53 publications
9
148
0
Order By: Relevance
“…Physical activity was measured by accelerometry counts based on a three-day sample with an Actigraph GT3X accelerometer (Actigraph LLC, Pensacola, FL) in a subset of participants (n=28) in order to assess the relative impact of physical activity on TEE (see Gurven et al 2013 for additional details).…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was measured by accelerometry counts based on a three-day sample with an Actigraph GT3X accelerometer (Actigraph LLC, Pensacola, FL) in a subset of participants (n=28) in order to assess the relative impact of physical activity on TEE (see Gurven et al 2013 for additional details).…”
Section: Methodsmentioning
confidence: 99%
“…Time allocation studies indicate that Tsimane women spend roughly 2 hours/day in direct productive tasks such as agricultural work and an additional 4-6 hours per day engaged in domestic tasks including childcare (Gurven et al, 2013). Gurven and colleagues used the factorial method (FAO/WHO/UNU, 1985) in conjunction with accelerometry and heart rate monitoring (Assah et al, 2011) to construct 24-hour physical activity level estimates (PAL) for Tsimane men and women.…”
Section: Methodsmentioning
confidence: 99%
“…They found that 24-hour PAL for Tsimane women (aged 20+) was 1.73. This PAL is categorized as “moderate to active” (FAO/WHO/UNU, 2004) and is only slightly higher than the mean PAL for women in industrialized societies (1.71), but slightly lower than that of women from other hunting and gathering or farming groups (Dugas et al, 2011; Gurven et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Based on analyses of modern human hunting and gathering populations [39,43], it is likely that foraging occurs at moderate aerobic intensities (~40–85% of maximum aerobic capacity) over long time periods, and thus, we might expect that physiological adaptations are tuned to this range of intensities. Since humans never had to adapt to long periods of inactivity, including very low amounts of moderate intensity activity, our physiological response to long-term inactivity can lead to chronic disease [26], and this may be especially relevant in the context of cognitive and brain aging.…”
Section: The Adaptive Capacity Modelmentioning
confidence: 99%